Anime-Watching Habits and Japanese Grammar (Bunpou) Achievement: an SLA-Based Mixed-Methods Study of Indonesian University Students - Aan Amalia (PT. Global Research Collaboration, 2026)
This study purposed to examine the correlation between anime-watching habits and Japanese grammar (bunpou) achievement among students enrolled in a Japanese Language Study Program. This study applied a mixed-methods approach using an explanatory sequential design. Quantitative data were collected through a questionnaire administered to 20 students from the Japanese Language Study Program at Universitas Widyatama and analyzed using the Pearson Product-Moment Correlation coefficient. Qualitative data were obtained from open-ended questionnaire responses and analyzed thematically to complement the quantitative findings. The results revealed no statistically significant correlation between anime-watching habits and grammar achievement (r = 0.002; p = 0.992), indicating that anime exposure does not directly influence students’ formal grammar performance. Nevertheless, the qualitative findings showed that anime contributes positively to students’ motivation, interest, vocabulary development, and cultural awareness in learning Japanese. Although anime-watching habits do not significantly contribute to Japanese grammar achievement, anime serves as an important motivational resource that encourages students’ engagement with Japanese language learning. Therefore, anime may be integrated into language instruction as a complementary learning resource rather than a primary means of grammar acquisition.